Epidemiological Features of Patients with Subdural Hygroma in a Prospective Case Series - Hamamoto Filho, Pedro Tadao; Pereira, Tamara Maria Ribeiro; Zanini, Marco Antonio (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2017)
Subdural hygroma is an accumulation of a cerebrospinal fluid-like fluid in the subdural space. It is a common epiphenomenon after a traumatic brain injury (TBI), but it may also occur after brain surgeries. A total of 17 patients in a prospective case series with subdural hygromas were analyzed. A male predominance (82.4%) was found. The mean age was 58.6 years. Traumatic brain injury was the main mechanism (76.5%); however, other mechanisms, such as post-craniotomy (17.6%), post-chronic subdural hematoma drainage (5.9%), and post-ventricle shunt (5.9%), were also observed. Incidental findings were diagnosed in 11.8% of the cases (mainly in elderly patients). Four patients required subdural shunt (23.5%)—all of them had TBI. Small subdural effusions were present in 35.5% of the cases. The mean time from admission to diagnosis was 6.1 days. The majority of the cases must have involved lesions of the dura–arachnoid interface since TBIs were the main causes of hygroma. The findings of incidental hygroma in elderly patients and its development after a ventricle shunt suggest that brain atrophy also plays a significant role in subdural hygroma formation.
Keywords: subdural hygroma; traumatic brain injury; cerebrospinal fluid; hydrocephalus